Mathematical operation and symbol notation
 Statements
P < Q > T,
R ≥ Q.
Conclusions
I. R > P
II. T < R

 if only Conclusion I is true
 if only Conclusion II is true
 if either Conclusion I or II is true
 if neither Conclusion I nor II is true
 if both Conclusion I and II are true

View Hint View Answer Discuss in Forum
Given that,
P < Q > T ...................(i)
R ≥ Q ......................(ii)
On combining the statements (i) and (ii), we get
P < Q ≤ R
R ≥ Q > T
Conclusions
I. R > P
II. T < RCorrect Option: E
Given that,
P < Q > T ...................(i)
R ≥ Q ......................(ii)
On combining the statements (i) and (ii), we get
P < Q ≤ R
R ≥ Q > T
Conclusions
I. R > P ...... (true)
II. T < R .......(true)
So, it is clear that both Conclusions I and II are true.
 Statements
F ≥ G = H;
G > J ≥ K
Conclusions
I. F ≥ K
II. K < H

 If only Conclusions I is true
 if only Conclusions II is true
 if either Conclusions I or II is true
 if neither Conclusions I nor II istrue
 if both Conclusions I and II are true

View Hint View Answer Discuss in Forum
Given that,
D > E ≤ F ............(i)
J < F ......................(ii)
On combining the statements (i) and (ii), we get
D > E ≤ F > J
Conclusions
I. D > J
II. E < JCorrect Option: D
Given that,
D > E ≤ F ............(i)
J < F ......................(ii)
On combining the statements (i) and (ii), we get
D > E ≤ F > J
Conclusions
I. D > J (false)
II. E < J (false)
So, it is clear that neither Conclusion I nor II is true
 Statements
P < Q = R ≥ S ≥ T
Conclusions
I. T ≤ Q
II. R > P

 If only Conclusions I is true
 if only Conclusions II is true
 if either Conclusions I or II is true
 if neither Conclusions I nor II is true
 if both Conclusions I and II are true

View Hint View Answer Discuss in Forum
Statements
P < Q = R ≥ S ≥ T
Conclusions
I. T ≤ Q
II. R > PCorrect Option: E
Statements
P < Q = R ≥ S ≥ T
Conclusions
I. T ≤ Q (true)
II. R > P (true)
Hence, both conclusions are definitely true.
 Statement
A ≤ B < C ;
A ≥ D;
C ≤ F
Conclusions
I. D < C
II. F ≥ D

 If only Conclusions I is true
 if only Conclusions II is true
 if either Conclusions I or II is true
 if neither Conclusions I nor II is true
 if both Conclusions I and II are true

View Hint View Answer Discuss in Forum
Statement
A ≤ B < C ;
A ≥ D ;
C ≤ F ;
On combining both the statements, we get
D ≤ A ≤ B < C ≤
Conclusions
I. D < C (true)
II. F ≥ D (false)
Hence, only conclusion I is definitely true.Correct Option: A
Statement
A ≤ B < C ;
A ≥ D ;
C ≤ F ;
On combining both the statements, we get
D ≤ A ≤ B < C ≤
Conclusions
I. D < C (true)
II. F ≥ D (false)
Hence, only conclusion I is definitely true.
 Statement
U > A = I ≤ 0 < E
Conclusions
I. I ≤ E
II. 0 > U

 If only Conclusions I is true
 if only Conclusions II is true
 if either Conclusions I or II is true
 if neither Conclusions I nor II is true
 if both Conclusions I and II are true

View Hint View Answer Discuss in Forum
Statement
U > A = I ≤ O < E
Conclusions
I. I ≤ E (false)
II. O > U (false)Correct Option: D
Statement
U > A = I ≤ O < E
Conclusions
I. I ≤ E (false)
II. O > U (false)
Hence, neither Conclusion I nor II is definitely true.